The Relationship Between Self-Concept and Cinderella Complex in Grade 11 Students in Vocational High School: Hubungan Antara Konsep Diri dengan Cinderella Complex Pada Siswa Kelas 11 di Sekolah Menengah Kejuruan - Ridaningsari, Adinda; Fahmawati, Zaki Nur (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the existence of the Cinderella complex phenomenon which often occurs in students of SMK X. This study aims to determine the relationship between self-concept and Cinderella complex in XI grade students of SMK X. This type of research used in this research is a quantitative method with a correlational approach. The variables contained in this study were self-concept as an independent variable and the Cinderella complex variable as the dependent variable. The population in this study was 380 students. The sampling technique used was purposive sampling technique. Retrieval of data using a Likert scale model, namely a self-concept scale with a reliability value of 0,797 and a Cinderella complex scale with a reliability value of 0,856. Retrieving data using a Likert scale model, namely the self-concept scale and the Cinderella complex scale. The analysis in this study obtained a correlation coefficient (rxy) of -0.630 with a significance value of 0.000 <0.05. It can be concluded that the hypothesis that has been proposed in this study is accepted, namely that there is a negative relationship between self-concept and Cinderella complex, which means that the higher the self-concept, the lower the Cinderella complex in class XI students of SMK X. Likewise, the lower the self-concept, the higher the Cinderella complex in class XI SMK X.